ANALISIS PENGARUH INVESTASI DAN KETENAGAKERJAAN TERHADAP PERTUMBUHAN EKONOMI REGIONAL DI KABUPATEN PELALAWAN - Putri Febyanti Agus; Syapsan '; Wahyu Hamidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
Economic growth is defined as an increase in the ability of an economy in producing goods and services. A high and sustainable growth is the main condition which indicates that economic development is running. Conduct analysis by multiple regressions. Independent variable methods used namely: Investment, Labor and the dependent variable is the economic growth.The result of this research indicate that the investment have significant effect to economic growth of Pelalawan Regency, while the labor of Pelalawan Regency haven’t significant effect on timeliness of econonimic growht. Based on the test result the coefficient of determination, the value of adjust R square of 39 % while the remaining 61 % is influenced by other variables aren’t include on this research.Keywords:Invesment, Labor, Capital Economic growth Pelalawan Regency.